2018
DOI: 10.1172/jci.insight.96672
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in hemodynamic forces initiate cardiac trabeculation

Abstract: Hemodynamic shear force has been implicated as modulating Notch signaling-mediated cardiac trabeculation. Whether the spatiotemporal variations in wall shear stress (WSS) coordinate the initiation of trabeculation to influence ventricular contractile function remains unknown. Using light-sheet fluorescent microscopy, we reconstructed the 4D moving domain and applied computational fluid dynamics to quantify 4D WSS along the trabecular ridges and in the groves. In WT zebrafish, pulsatile shear stress developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(129 citation statements)
references
References 47 publications
15
114
0
Order By: Relevance
“…Polacheck et al demonstrated that physiological shear stress activates NOTCH1 to regulate the composition of adherens junctions and thereby control vascular permeability 14 . Consistent with this, Notch is also activated by physiological HSS during development to permit arterial differentiation 13,36,37 , cardiac morphogenesis 38,39 and valve formation 40 and is also activated by HSS in adult arteries to protect them from atherosclerosis 15 . The expression of JAG1 is also enhanced in HUVEC exposed to shear stress compared to static conditions 41 .…”
Section: Jag1/notch4 Mechanosensingmentioning
confidence: 58%
“…Polacheck et al demonstrated that physiological shear stress activates NOTCH1 to regulate the composition of adherens junctions and thereby control vascular permeability 14 . Consistent with this, Notch is also activated by physiological HSS during development to permit arterial differentiation 13,36,37 , cardiac morphogenesis 38,39 and valve formation 40 and is also activated by HSS in adult arteries to protect them from atherosclerosis 15 . The expression of JAG1 is also enhanced in HUVEC exposed to shear stress compared to static conditions 41 .…”
Section: Jag1/notch4 Mechanosensingmentioning
confidence: 58%
“…The application of Saak transform to segment 3-D LSFM-acquired images creates an opportunity to investigate chemotherapyinduced cardiac structure and mechanics. Previously, we needed to perform manual or semi-automated segmentation to reconstruct LSFM architectures for computational fluid dynamics [15,16] and interactive virtual reality [17,18]. The addition of edge detection to Saak transform enables the calculation of surface area in relation to the volume of myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Light-sheet fluorescence microscopy (LSFM) is instrumental in advancing the field of developmental biology and tissue regeneration [1][2][3][4]. LSFM systems have the capacity to investigate cardiac ultra-structure and function [5][6][7][8][9][10][11][12][13][14], providing the moving Baek, Zhaoqiang Wang, Mehrdad Roustaei, Dengfeng Kuang, C.-C. Jay Kuo †, and Tzung K. Hsiai † boundary conditions for computational fluid dynamics [15,16] and the specific labeling of trabecular network for interactive virtual reality [17,18]. However, efficient and robust structural segmentation of cardiac trabeculation remains a post-imaging challenge [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…HAEC migration assay was performed as previously described. 9 Areas between inner borders of HAEC at 4, 6, 12, 24 hours post scratch were evaluated using ImageJ. Supplemental Figure 6F shows a schematic representation of how HAEC migration was quantified.…”
Section: Ec Migration and Matrigel Tube Formation Assaymentioning
confidence: 99%
“…7 During cardiac morphogenesis, WSS induces the Notch1-ephrinb2-neuregulin 1/erb-b2 receptor tyrosine kinase 2 signaling pathway to initiate cardiac trabeculation. 8,9 Pulsatile and oscillatory WSS differentially regulate Delta/Serrate/Lag ligands in vascular endothelium and smooth muscle cells. 10 The transmembrane ephrinb2 ligand mediates developmental angiogenesis and arteriovenous specifications.…”
Section: Introductionmentioning
confidence: 99%